PERANCANGAN PERBAIKAN KUALITAS PADA PRODUK LDAM 000400-0 MENGGUNAKAN METODE SIX SIGMA DI PT SOHOU KIKAKU INDONESIA - Bagaskara Pradana, Raditya
PT Sohou Kikaku Indonesia is a manufacturing company in the metal machining sector, producing a variety of machined products such as brake handles, various fasteners, hinges, brackets, and others. These products must consistently maintain quality in accordance with ISO 9001:2015 standards. PT SKI aims to reduce defective products to 0.2% across all products. However, in 2023, there was a product with the highest defect rate, reaching up to 14.55%, specifically the LDAM 000400-0. This defect rate exceeds the target, resulting in losses for the company. Therefore, a quality improvement initiative was undertaken for LDAM 000400-0 product using Six Sigma methodology with the DMAIC (Define, Measure, Analyze, Improve, Control) approach to reduce the defect rate.